adasdasd - Dewi Aryanti; Novi Indriani; Irir Khairiyah; Irma Nuraini; yudi Triguna; Novi Enis Rosuliana; Peni Cahyati; Syaukia Adinia; Sofia Februanti; Tetet Kartilah (LP4M STIKes Karsa Husada Garut, 2025)
Anemia in adolescent girls is a public health issue that affects quality of life, academic achievement, and increases the risk of problematic pregnancies and stunting in the future. Adolescent girls in madrasahs in rural areas are more vulnerable due to limited nutritional knowledge, low compliance with Iron and Vitamin A Supplement (IVAS) consumption, and strong myths surrounding IVAS. This community service activity aims to improve adolescent girls' knowledge, attitudes, and skills in consuming TTD through distribution assistance and comprehensive education. The target of the activity is 56 eighth-grade MTs students in Sukaratu District, Tasikmalaya Regency, most of whom are also santri (Islamic boarding school students). The method used a participatory educational approach through brainstorming, material delivery, discussion, practice of taking TTD and independent recording, as well as simple pre- and post-tests over two days. The first day focused on exploring initial knowledge, clarifying facts and myths, the benefits of TTD, sources of iron, and the correct methods of consumption and recording. The second day evaluated participants' ability to explain anemia and TTD in their own words, practice consumption and recording, and identify ways to overcome uncomfortable side effects. The results of the activity showed an increase in enthusiasm and understanding; the majority of students were able to articulate the concepts of anemia, the benefits of TTD, and self-recording. Cross-sector collaboration.